The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3846/16484142.2011.565599
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Before and After Crash Features Into Measuring the Effectiveness of Intersection Safety Improvement Project in Harbin / Prieš Ir Po Eismo Įvykio Atsiradusių Padarinių Visuma, Vertinant Saugaus Eismo Sankryžose Projekto Efektyvumą Charbino Mieste / Учет Совокупности Факторов, Возникающих До И После Дорожно-Транспортного Происшествия, Для Оценки Эффективности Проекта По Безопасному Движению На Перекрестках В Городе Харбине

Abstract: Many studies focused on the analysis of effect factors contributing to the crashes and development of crash prediction models have resulted in aggregate researches to quantify the safety effects of geometric and traffic variables and environmental concerns on the expected outcome of fatal, injury and/or property damage losses at specific locations. Crash insight regarding different locations, however, has rarely been performed. Such investigations are useful for at least two reasons. First, there is a priori n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Discrepancy in Malaysian accident data has been highlighted in previous research [2]. Other low and middle-income or developing countries also experience similar problems related to their accident data such as China [3], South Africa [4] and Saudi Arabia [5]. Accumulation of errors in the accident data starts with the incorrect or incomplete filling of an ARF.…”
Section: Introductionmentioning
confidence: 76%
“…Discrepancy in Malaysian accident data has been highlighted in previous research [2]. Other low and middle-income or developing countries also experience similar problems related to their accident data such as China [3], South Africa [4] and Saudi Arabia [5]. Accumulation of errors in the accident data starts with the incorrect or incomplete filling of an ARF.…”
Section: Introductionmentioning
confidence: 76%
“…Intersection safety has been becoming an international concern. In Australia, almost 33% of major casualties are caused by intersection crashes [1]. In China, approximately 30% of total road fatalities happen at intersections [2].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other locations in a roadway network, intersections are obviously more prone to be involved in traffic crashes, especially passenger-and bicyclist-involved crashes, due to the substantial factors in complex traffic environment, but how these different factors affect the occurrence and severity of crashes is still unclear (Wang et al, 2001a;Wang et al, 2011b;Delmelle et al, 2012;Siddiqui et al, 2014). Torbic et al (2010) reported that intersections with more lanes had highest vehicle-pedestrian crashes and that crash frequency was highest when the ratio of minor road AADT to major road AADT was highest.…”
Section: Introductionmentioning
confidence: 99%